Deployments Scenarios of 5G Networks - Oudah, Ali A. (2017)
Traditionally, interference and coexistence studies of cellular systems tackle their emerging issues without taking into account their duplex modes. Nevertheless, for duplex-based networks in general and for Long Term Evolution (LTE) in particular, it is quite important to consider the impact of duplex modes of both interfered and interfering cells on total emitted inter-cell interference power encountered. LTE, as a fourth generation radio, supports both Frequency Division Duplex (FDD) and Time Division Duplex (TDD) schemes, while half-duplex mode being additional option introduced to LTE in certain network operations. In this work, the imapact of inter-duplexing overlap is analyzed and account for in the total emitted interference. Coexistence guidelines in 2.6 GHz frequency band will be also given and explained.